Design and Analysis of Axial Thrust Roller-Exciting Vibrating Table and Its Motor-Control System Based on Co-simulation - 吴上生 陆振威 黄泽星 周运岐 (东华大学学报（英文版）, 2015)
Aiming at improving the mechanical vibrating equipment,the axial thrust roller-exciting vibrating tables and its motor-control system based on co-simulation were put forward. First, the structures of vibrating table and its surface equations and boundary conditions were established through reversal process. Second,waveform distortion influenced by random and harmonic waves was analyzed by equivalent parametric transition. These two steps were both technological challenge and contribution for the vibrating table.Finally, based on research above, a proportion integration differentiation（ PID） motor-control system was built to show its rapid operation and convenient control. All the results show that not only does vibrating table have lower waveform distortion than traditional ones,but its control system narrows down the fluctuation and improves anti-interference performance. Hence,it provides a more extensive selection for efficient and practical mechanical vibrating table.